Комплексна оцінка стану популяцій Iris pumila L. України - Бублик, О.М.; Андрєєв, І.О.; Парнікоза, І.Ю.; Троїцька, Т.Б.; Кунах, В.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. Iris pumila L. (Iridaceae), typical steppe xerophyte, which is protected in several regions of Ukraine. Area of the species range has suffered a significant decline and fragmentation over the recent centuries. The comprehensive population studies were conducted to elucidate the effects of these processes and determine the indices that can be used as well-timed signals of species extinction risk. Methods. Ecological and population studies were combined with ISSR-analysis of genetic diversity to characterize the populations of I. pumila. Results. A number of population and ecological indicators suggests that I. pumila in Ukraine may be referred to regressive species threatened by genetic erosion. Moreover, the results of ISSR-analysis of plants from four populations in Mykolayiv and Poltava regions showed relatively high levels of the species genetic diversity and weak divergence of isolated populations. Conclusions. The reduction and fragmentation of I. pumila habitat first of all is accompanied by decline in ecological and population indicators, but depletion of the populations’ gene pool occurs much slower. To adequately determine the risk of genetic erosion in particular species, apart from assessment of population and ecological indicators, evaluation of species genetic resources using molecular markers is needed.